Stabilizing Blood Sugar Levels in Type 2 DM Patients by Providing Benson Relaxation Therapy Combined with Dhikr Based on Self-Care Orem - Zahrotul Jannah; Umdatus Soleha; Abdul Muhith (Journal Of Nursing Practice, 2024)
Background: People with diabetes mellitus experience hyperglycemia, the higher the likelihood of complications if do not get the right treatment immediately. In addition, people with diabetes mellitus are prone to stress because the disease is difficult to cure and patients must take medications every day. Therefore, proper management is needed. Purpose: The purpose of this study is to determine the effect of self-care orem-based dhikr combination benson relaxation therapy  on blood sugar levels in type 2 diabetes mellitus patients in the Ujungpangkah Gresik Health Center Working Area. Method: This type of research uses Quasy Experiment with Pretest Posttest Control Group Design. The sample in this study was 46 respondents, which were divided into 2 groups, namely 23 respondents for the control group and 23 respondents for the intervention group. The independent variable of this study was benson relaxation therapy combined with dhikr, while the dependent variable was blood sugar levels. The data were analyzed using paired T-Test and Independent T-test tests on blood sugar level variables with kemaknaan α=0,05. Results: The results of the independent t-test on the variable of blood sugar levels with a significant level of 0.000 < α = 0.05, showed that there was an effect of the administration of benson relaxation therapy combined with dhikr on blood sugar levels in type 2 DM patients. Conclusion: The conclusion of this study is that benson relaxation therapy combined with dhikr has an effect on blood sugar levels in patients with type 2 diabetes mellitus. In the future, it is hoped that health workers can increase the provision of information and education evenly to health service places.